To the edge of the world : the story of the trans-siberian express, the world's greatest railroad - Wolmar, Christian (Public Affairs, 2013)
To the Edge of the World is an adventure in travel--full of extraordinary personalities, more than a century of explosive political, economic, and cultural events, and almost inconceivable feats of engineering. Christian Wolmar passionately recounts the improbable origins of the Trans-Siberian railroad, the vital artery for Russian expansion that spans almost 6,000 miles and seven time zones from Moscow to Vladivostok. The world's longest train route took a decade to build--in the face of punishing climates, rampant disease, scarcity of funds and materials, and widespread corruption.